Farm Monitoring Mobile Robot Speed Controlled of DC Motor Driver System Using PID Controller. (International Journal of Engineering and Computer Science, 2015)
The ARM Based controller for DC motor Drive system for mobile robot which are used for The farm environment and plant condition such as temperature, humidity soil moisture content etc. are continuously monitored through suitable data acquisition system incorporated in the robotic system. A DC motor based robotic arm is designed for collecting soil sample and test various soil parameters. A closed loop feedback algorithm based on Digital PID controller has been developed for precise position and speed control of mobile robot. A mobile Robotic system for monitoring these parameters using wireless network has been developed based on ARM platform. Robotic platform consists of ARM7 based LPC 2148 processor, Motor driver, robot mechanical assembly .The multi-sensor measurement over a wireless connectivity for various distances. From an application point of view, a mobile robotic platform is developed to test the multi-sensor embedded system for Agro- Industrial Applications. The indoor and outdoor range for wireless transmission has been presented. It is observed that for better transmission of signals via wireless communication, the low frequency along with low baud rate and line of sight range is required to minimize the signal loss.